The Records of John Glassford and Company Containers 12-14
Ledgers, journals, daybooks, inventories, cashbooks, letterbooks of the various mercantile firms in Maryland and Virginia representing or succeeding the Glasgow, Scotland, firm of John Glassford and Company in the Chesapeake tobacco trade.